Memanfaatkan AI untuk Storytelling: Panduan Praktis untuk Content Creator pada Yayasan Kelurahan Banjarsari - Galih Setiawan Nurohim; Budi Al Amin; Diah Pradiatiningtyas (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
In this fast-paced time, the relationship between content creators and audiences can be built using storytelling and quality content as an attraction. Along with the emergence and development of technology, AI or Artificial Intelligence now facilitates the creative process for content creators. AI can assist from drafting, visuals, to editing. This article aims to directly explain how AI can help improve efficiency, generate ideas, and expand ways of telling a story. However, when integrating AI into the creative process, there are limitations that must not lose the personal touch and creative flair that make a story feel meaningful and remain authentic. Content creators are able to use human insight and the sophistication of AI to produce stronger, more innovative, and relevant storytelling amidst increasingly fierce digital competition.